2021
DOI: 10.1108/lodj-01-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

The effects of shared leadership on team performance

Abstract: PurposeThis study aims to investigate the relationship between shared leadership and team performance at the team level. Drawing on conservation of resources (COR) theory, the authors examine whether shared leadership is associated with team performance through team positive psychological capital (PsyCap). This study further examines whether task-oriented and relationship-oriented shared leadership affect team performance differently.Design/methodology/approachMulti-source survey data were obtained from 92 tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 59 publications
3
25
2
Order By: Relevance
“…If this is transferred to the present sample of the study, in which shared leadership is recorded as an emergent phenomenon in primarily hierarchical organizational structures, one explanation for the negative correlation could be that team members have the expectation that relations-oriented leadership behaviors will continue to be adopted by the official leader and therefore evaluate it as negatively, when these are taken over by team members. Interestingly, Han et al (2021) also found the opposite effect for relations-oriented behaviors. Here, they postulate a positive relationship mediated through team psychological capital.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…If this is transferred to the present sample of the study, in which shared leadership is recorded as an emergent phenomenon in primarily hierarchical organizational structures, one explanation for the negative correlation could be that team members have the expectation that relations-oriented leadership behaviors will continue to be adopted by the official leader and therefore evaluate it as negatively, when these are taken over by team members. Interestingly, Han et al (2021) also found the opposite effect for relations-oriented behaviors. Here, they postulate a positive relationship mediated through team psychological capital.…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, we chose to use self-ratings variables in this study to gain insight into individual experiences with shared leadership. This could also be a reason for conflicting results with previous studies on behavioral dimensions, such as Han et al, 2021. Future studies looking at employees' experiences with shared leadership should be expanded, for example, by measuring performance with additional objective sources. This in turn implies that a multilevel approach should be considered when examining shared leadership behaviors to supplement research on the effects of shared leadership behaviors on team outcomes.…”
Section: Limitations and Future Directionsmentioning
confidence: 94%
See 1 more Smart Citation
“…Two studies on shared leadership were conducted in 2021. Han et al. (2021) discovered that shared leadership can affect team performance while Liu et al.…”
Section: Resultsmentioning
confidence: 99%
“…Han et al (2021) discovered that shared leadership can affect team performance whileLiu et al (2022) found that shared leadership affect team members to act on their own initiative and be creative. In 2018, Ribeiro et al studied the effect of authentic leadership on corporate citizenship behaviour, staff innovation as well as personal performance Scheepers and Storm (2019).…”
mentioning
confidence: 99%